(POST) CIVILIZATION OF FEAR (Годишен зборник на Филозофски факултет - Скопје, 2021)
The main objective of this text is to give a presentation/interpretation/comment on several philosophical authors and their philosophical scientific works, which in any direct or indirect way explore/reflect on the phenomenon of fear that controls the human unconsciousness/ sub-consciousness/ consciousness, starting from antiquity to the present day, when man lives in a (post)modern/ post-human urban civilization/ culture. The current pandemic of Covid 19 is just an occasion to start from a series of older philosophers and scientists, who explicitly or implicitly warned of the dangers of the emergence of such and similar pandemics and the occurrence of new and unforeseen human situations, in which civilization found itself as a result of the spread of deadly diseases of all kinds. The main focus is on several (four) contemporary philosophers: Giorgio Agamben, Slavoj Žižek, Lieven De Cauter, and Lars Svendsen.In the final part of the text, instead of the usual conclusion, and with previous own incidental remarks and comments, the author gives his short critical comment on the views and philosophical/scientific predictions of the authors, who are the subject of his philosophical and scientific criticism.